Aminoclay‐Graphene Oxide Composite for Thin‐Film Composite Reverse Osmosis Membranes with Unprecedented Water Flux and Fouling Resistance. Issue 20 (19th September 2021) - Islam, Md Rabiul; Khurana, Pratishtha; Srikrishnarka, Pillalamarri; Nagar, Ankit; Jash, Madhuri; Jenifer, Shantha Kumar; Ganayee, Mohd Azhardin; Kumar, Mathava; Pradeep, Thalappil
Abstract: Present work attempts to incorporate aminoclay‐graphene oxide composites into thin‐film composite (TFC)‐reverse osmosis membranes to improve the desalination efficiency of brackish water. The composite is coated on a polysulfone substrate as a result of interfacial polymerization of m‐phenylene diamine and trimesoyl chloride, at different time durations. The prepared membranes are analyzed for their water permeation and salt rejection efficiencies using brackish feed water. The results indicated that the membrane loaded with 0.015 wt% of the composite delivered maximum flux at 20 bar pressure for 2000 ppm feed. Moreover, the water flow rate increased by ≈3.27 times (from 15.62 ± 0.36 to 50.28 ± 1.69 Lm –2 h –1 ), compared to the unmodified TFC membrane. An enhancement in the salt rejection from 97.03 ± 1.07 to 99.51 ± 0.10% is also observed for the same feed water at 20 bar as compared to the unmodified membrane. Furthermore, antifouling tests with model bio‐foulant humic acid revealed better stability and antifouling performance of the prepared membranes than the unmodified membranes under identical operating conditions. The membrane, therefore, assures high performance and lifetime owing to its mechanical and chemical stability, and hence suggests energy‐efficient desalination. Abstract : The effect of incorporating aminoclay‐graphene oxide composite into thin‐film composite (TFC)‐reverse osmosis membranes is investigated to improve the desalination efficiency of brackish water. For the optimized modified membrane (M30) the flux increased ≈3.27 times compared to the unmodified TFC membrane at 20 bar pressure for 2000 ppm feed sodium chloride solution.